A Survey on the Latest Intrusion Detection Datasets for Software Defined Networking Environments - Khalid, Harman Yousif Ibrahim; Aldabagh, Najla Badie Ibrahim (Engineering, Technology & Applied Science Research, 2024)
Software Defined Networking (SDN) threats make network components vulnerable to cyber-attacks, creating obstacles for new model development that necessitate innovative security countermeasures, like Intrusion Detection Systems (IDSs). The centralized SDN controller, which has global view and control over the whole network and the availability of processing and storing capabilities, makes the deployment of artificial intelligence-based IDS in controllers a hot topic in the research community to resolve security issues. In order to develop effective AI-based IDSs in an SDN environment, there must be a high-quality dataset for training the model to offer effective and accurate attack prediction. There are some intrusion detection datasets used by researchers, but those datasets are either outdated or incompatible with the SDN environment. In this survey, an overview of the published work was conducted using the InSDN dataset from 2020 to 2023. Also, research challenges and future work for further research on IDS issues when deployed in an SDN environment are discussed, particularly when employing machine learning and deep learning models. Moreover, possible solutions for each issue are provided to help the researchers carry out and develop new methods of secure SDN.